Onchocercosis, endemic eradicated in Ecuador. - Alvear L, José Miguel (Revista Universidad de Guayaquil, 2015)
ONCHOCERCOSIS, also known as “River Blindness” is a disease produced by the ONCHOCERCA VOLVULUS, a filarial nematode (worm) hosted by the black fly Simulium.  Millions of persons are still affected and thousands blind from the infection, in the tropics. The fly introduces the larvae in the skin were develops into microfilariae that invades blood, urine, conjunctiva, etc. Adult female worms live for years in nodules within connective tissue, producing microfilariae by the millions. The nodules, single or multiple are painless, movable, frequently located over bony prominences. The blindness is related to the head invasion and density of the microfilariae near the eye. Microfilariae live between 6 months and two years only and during that time invade skin and connective tissue. The great majority of microfilariae dye in the infected skin producing severe chronic dermatitis, keratitis, retinitis and blindness.Surgical excision of the nodules is mandatory to decrease blindness and improve general condition, besides the medical treatment with Ivermectine (Merck). Some male patients develop huge inguinal hernias (connective tissue degeneration of the abdominal wall) which requires surgical treatment as well. This endemic in Ecuador has been eradicated in September 2014, 40 years later after the initial efforts and protagonists mentioned
Keywords: Filariosis; Black fly; Tropical endemics; Blindness; Dermatitis severe; Subcuticular nodules; Inguinal hernias gigantic